PENGARUH KUALITAS AUDITOR, SISTEM PENGENDALIAN INTERNAL DAN KOMITE AUDIT TERHADAP AUDIT DELAY PADA KANTOR AKUNTAN PUBLIK SE KOTA MAKASSAR - Andi Indira Alfitasari Nur Palulu; Abdul Rahman Mus; Darwis Lannai (Magister Akuntansi, Universitas Atma Jaya Makassar, 2018)
The purpose of this study was to analyze the effect of auditor quality on audit delay in KAP in Makassar City, to analyze the effect of the internal control system on audit delay in KAP in Makassar City, to analyze the influence of audit committees on audit delay in KAP in Makassar City. To implement these objectives, data collection techniques are used through questionnaires, while data analysis techniques are used validity test, reliability test, classic assumption test, multiple linear regression analysis and hypothesis testing. The results showed that the effect of auditor quality with audit delay, it can be concluded that the auditor's quality has a positive and significant effect on audit delay in several public accounting firms throughout the city of Makassar. The influence of the internal control system with audit delay, it can be concluded that the internal control system has a positive and significant influence on audit delay in several public accounting firms throughout the city of Makassar. The influence of the audit committee with audit delay, it can be concluded that the audit committee has a positive and significant influence on audit delay in several Public Accounting Firms in the city of Makassar. From the results of regression testing it can be concluded that the dominant variable influencing audit delay in several Public Accounting Firms in the city of Makassar is the internal control system.